Compensation to Managers of Charitable Organizations: An Empirical Study of the Role of Accounting Measures of Program Activities - Baber, William R.; Daniel, Patricia L.; Roberts, Andrea A. (The Accounting Review, 2002)
We investigate how unique features of charities affect the manner in which they compensate their executives. We find that changes in compensation are significantly positively associated with changes in spending on programs that advance organization objectives, whether changes in program spending are attributable to changes in revenue raised or to changes in the relative costs of administering the charity. The results suggest that accounting performance measures can play a role in nonprofit organizations whose objectives are typically subjective and nonfinancial, and thus, whose progress toward objectives is difficult to quantify.